Low-Cost Fruit Sanitization Using ESP Module - Dr. L. B. Chaudhari; Snehal Kapse; Vaibhav Bathe; Somesh Sakhare; Shubham Mahadik (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Ultraviolet-C (UV-C) irradiation has emerged as a powerful, chemical-free method to inactivate a wide range of pathogens on everyday objects. This project details the design and implementation of a compact sterilization box driven by an ESP32 microcontroller. An infrared sensor ensures the UV-C lamp operates only when the enclosure is securely closed, while a relay module switches the high-voltage lamp on and off under microcontroller control. Real-time user feedback is provided via a 16×2 LCD display showing system status and a countdown timer, and an audible buzzer signals cycle completion. The hardware and firmware were developed using readily available components and the Arduino IDE, emphasizing ease of assembly and cost-effectiveness. Safety and usability tests confirmed that the lid interlock reliably prevents accidental UV exposure, and the system maintained stable operation across multiple consecutive sterilization cycles. Although full microbial assays remain ongoing, established literature supports that a 60-second exposure at 254 nm achieves > 99.9 % pathogen inactivation. Future enhancements include IoT connectivity for remote monitoring, data logging for maintenance scheduling, and multiple sterilization modes to accommodate varied item sensitivities, positioning the device for both household and small-scale commercial applications.